DNA and Non-Replicating Human Adenovirus Vectors Expressing VP2 Protein of Infectious Bursal Disease Virus Induce Humoral Immunity in the Murine Model - Romanutti, Carina (2021)
An eukaryotic expression Plasmid (pXL) and a replica- tion-defective human adenovirus serotype 5 (Ad5) carry- ing the coding sequence of mature VP2 protein from Infec- tious Bursal Disease Virus (IBDV) were constructed and the evaluation of their immunogenicity was carried out in the murine model. These novel recombinant vectors were able to express VP2 protein in cell cultures and to induce IBDV- seroneutralizing antibodies in mice vaccinated with heter- ologous prime-boost regimen. To our knowledge, this is the first report on the obtaining of a recombinant Ad5 vector expressing VP2 protein of IBDV. Other experiments will be performed to evaluate its usefulness in the chicken, natural host of IBDV.